Decree of the President of the Arab Republic of Egypt by Law No. 1 of the Year 2015 Amending some Provisions of Law No. 10 of the Year 1990 Concerning the Expropriation of Properties for Public Benefit = قرار رئيس جمهورية مصر العربية بالقانون رقم 1 لسنة 2015 بتعديل بعض أحكام القانون رم 10 لسنة 1990 بشأن نزع ملكية العقارات للمنفعة العامة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic